ChemInform Abstract: A Rhodium Catalyst for Single‐Step Styrene Production from Benzene and Ethylene. Issue 39 (September 2015) - Vaughan, Benjamin A.; Webster‐Gardiner, Michael S.; Cundari, Thomas R.; Gunnoe, T. Brent
Abstract The catalyst RAB is found to be optimal for the selective preparation of styrene in a high yield.